Transportable Mononuclear Metal Atoms as Building Blocks for Bottom‐up Material Fabrication: Pt1(0) and Au1(0) Atoms in Stock Solutions. Issue 8 (5th May 2020) - Li, Huixiang; Liang, Changhui; Gao, Pan; Hou, Guangjin; Liu, Kairui; Liu, Wei; Jiang, Qike; Bai, Shi; Zhang, Z. Conrad
Abstract: Premade and readily transportable mononuclear zero‐valent metal atoms in stock solvents offer the potential capability for bottom‐up designable metallic material fabrication. This work demonstrates a potentially universal and practical strategy to prepare weakly shielded mononuclear metal atoms in a volatile solvent, which also constitutes a strippable ligand to the metal atoms. Herein, M1 (0) (M=Pt, Au) atoms are prepared by reducing H2 PtCl6 and HAuCl4 with ethanol in ethylene glycol diethyl ether (EGDE) under mild temperatures. The diether oxygens of EGDE, H +, and Cl − coordinating to the M1 (0) atoms, make the M1 (0) atoms stable in the solvent under low pH. However, the M1 (0) atoms can be released either by evaporation of HCl and EGDE or through neutralization of the HCl with a base. The premade M1 (0) atoms can be used as primary building blocks to construct designable materials. To demonstrate a potential application, the M1 (0) atoms are conveniently transported onto the surface of TiO2 through impregnation followed by mild heating. The atomic dispersion and reduced state of the metal atoms are well preserved, as verified by HAADF‐STEM images, XPS, and DRIFT spectroscopy. Abstract : In stock : Stock solutions of reduced mononuclear M1 (0) (M=Pt, Au) atoms are prepared from their chloride salt precursors in removable solvent glycol ether/ethanol/H2 O. Glycol ether and HCl function as strippable shields prevent M1 (0) atoms from aggregation. The releasable M1 (0) atoms suit as building‐blocks for designable bottom‐up material fabrications. Specifically, M1 (0) atoms are readily transported onto the TiO2 surface and remain in the reduced mononuclear state.